Estudio de prefactibilidad para la instalación de una planta procesadora de hojuelas a base de numia (Phaseolus vulgaris) y tarwi (Lupinus mutabilis) - Vasquez Torreblanca, Erick Manuel (2021)
This research presents a pre-feasibility study for the installation of a numia and tarwi cereal processing plant, where the technical, economic, financial and market viability will be evaluated. Target market will be B and C sectors of Metropolitan Lima which constitute more than 60% of the population; likewise, the focus of this project are people who have a healthy lifestyle or healthy eating habits. As a conclusion of the market research, the demand of the project is determined to be 195 647 500 gr cereal bags for the fifth year of operation, on the other hand, thanks to the surveys made to 200 people, it could be determined that the ideal product presentation weight is 500 gr while the ideal price is 18 soles.